Increasing medical student numbers in resource constrained settings: Ethical and legal complexities intersecting patients' rights and responsibilities. Issue 2 (10th November 2020) - Menezes, Colin; Dhai, Ames
Abstract: There is a need to increase the number of practicing medical doctors in South Africa. We examine the ethical implications of patients' rights being affected in medical education in a South African context. The South African legal framework advocates public healthcare access. Yet, the State's ethical obligations when it comes to guaranteeing public healthcare access, conflict with its utilitarian policy, that allows for medical education to help achieve the State's public healthcare commitments, at the cost of eroding patients' rights, and accepts that certain actions are imperative, in line with Ubuntu, which is tenable yet nuanced. A patient treated by a licenced doctor today, benefits because other patients have allowed themselves to be used as hands‐on learning material for medical students yesterday. Healthcare institutions need to take cognisance of the numbers of medical students that patients can reasonably be expected to endure. There is a need for the Health Professions Council of South Africa and medical schools to adopt guidelines on reasonable levels of medical student‐patient interaction, and medical student‐to‐patient ratios in healthcare delivery.